Augmenting Drainage System in the Old Town of Kuching, Sarawak, Malaysia - Yau Seng Mah, Darrien; Ong King Ngu, Johnny; Liew, Vernon; Hashim Wan Ibrahim, Wan (International Journal of Engineering and Technology, 2018)
Padungan, one of the busiest business districts within Kuching City has been facing difficulties due to its age and inability to manage urban runoff. To sustain its historical heritage value without compromising the beauty and ability to discharge urban runoff, environmental needs have called for a change in urban stormwater management. The main objective of this study is to incorporate StormPav Green Pavement along the backstreet of Padungan and to investigate the effectiveness of the permeable road. The methodology used in this study is by means of computer modelling using Storm Water Management Model (SWMM). There are two models built, simulating conditions as (a) current drainage system facility; (b) implementing StormPav Green Pavement along the back of Padungan Street for the purpose of accommodating runoff from the whole two rows of buildings. From the analysis of modelling scenes, implementing the permeable road is a preferable solution as it encompasses both the present and future needs into the design consideration.Â Â